Information System Model for Curriculum Management Base on National Educational Standards in Thai Supply Chain - Artaphon Chansamut (ExcelingTech, 2022)
The obiective of the research was to develop and to evaluate information system model for curriculum management base on national education standards in Thai supply chain. The samples are ten experts in the field of information system and supply chain. The data is analysed by means and standardized deviations. The research result shows that the model consists of five elements namely main components, Suppliers, Manufacturer, Customers, Consumers The assessment of pattern using Black-Box technique . An evaluation result from expert agreement about information system model for curriculum management base on national education standards in Thai supply chain was a high level and can support aN information system development.